Subsidi Angkutan Udara Kargo Dalam Kerangka Program Jembatan Udara Sebagai Kewajiban Pelayanan Publik Di Indonesia - Afif, Muhammad Ikram (Jurnal Hukum & Pembangunan, 2023)
The state is obliged to subsidize cargo air transport to Air Transport Business Entities in the form of State-Owned Enterprises (SOEs) and non-SOEs. This provision is carried out by the application of public service obligation through the Air Bridge program carried out by the government through assignments to SOEs and/or private Air Transport Business Entities through the selection of other service providers in accordance with statutory provisions. This study attempts to analyze the problems related to the implementation of subsidized cargo air transport as a public service obligation based on the legal framework of public services in Indonesia; comparison of the implementation of cargo air transport subsidy in Indonesia with the implementation of public service obligation in the European Union, Malaysia and Australia; and the connection between the application of cargo air transport subsidy to non-SOEs Air Transport Business Entities with the framework of public service obligations in Indonesia.